2023
DOI: 10.1161/atvbaha.123.319385
|View full text |Cite
|
Sign up to set email alerts
|

ANG2 Blockade Diminishes Proangiogenic Cerebrovascular Defects Associated With Models of Hereditary Hemorrhagic Telangiectasia

Xingyan Zhou,
Jenna C. Pucel,
Aya Nomura-Kitabayashi
et al.

Abstract: BACKGROUND: Hereditary hemorrhagic telangiectasia (HHT) is a vascular disorder characterized by arteriovenous malformations and blood vessel enlargements. However, there are no effective drug therapies to combat arteriovenous malformation formation in patients with HHT. Here, we aimed to address whether elevated levels of ANG2 (angiopoietin-2) in the endothelium is a conserved feature in mouse models of the 3 major forms of HHT that could be neutralized to treat brain arteriovenous malformations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 88 publications
(173 reference statements)
1
9
0
Order By: Relevance
“…19 Comparative RNA sequencing analyses of isolated brain ECs from Smad4-iEC.KO , Eng-iEC.KO , and Alk1-iEC.KO mice revealed a common proangiogenic transcriptional profile associated with HHT. 1 This genetic fingerprint was in agreement with an upregulation of Ang2 in brain vessels and a downregulation of its receptor Tek/Tie2 in HHT mice compared with controls. Accordingly, a reduction of Tek signaling was also observed in vitro using human ECs mimicking the HHT2 condition.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…19 Comparative RNA sequencing analyses of isolated brain ECs from Smad4-iEC.KO , Eng-iEC.KO , and Alk1-iEC.KO mice revealed a common proangiogenic transcriptional profile associated with HHT. 1 This genetic fingerprint was in agreement with an upregulation of Ang2 in brain vessels and a downregulation of its receptor Tek/Tie2 in HHT mice compared with controls. Accordingly, a reduction of Tek signaling was also observed in vitro using human ECs mimicking the HHT2 condition.…”
supporting
confidence: 76%
“…16 Thus, increased expression of Ang2 induced by the GNAQ variant p.R183Q in human ECs was found to drive the formation of enlarged blood vessels in mice, while knockdown of Ang2 in ECs carrying the GNAQ /R183Q variant normalized the size of the vessels. 17,18 As a follow-up to the above findings, now Zhou et al 1 have further analyzed and confirmed the regulated expression and function of Ang2 not only in Smad4-iEC.KO but also in Eng-iEC.KO and Alk1-iEC.KO mouse models of HHT (Figure). In this case, the authors centered their studies on brain ECs and brain AVMs, a goal justified by the fact that ≈10% to 20% of patients with HHT present with brain AVMs.…”
mentioning
confidence: 60%
See 3 more Smart Citations